Magnesium ocular injury - A case report - Andrea Little; Megan Dietze-Fiedler; Colton Fernstrum; Norberto Mancera; Richard Wilcox; Viet Do (Elsevier, 2021)
Common agents described in ocular chemical and thermal injuries include cleaning agents, fertilizers, refrigerants, cement, preservatives, and fireworks. Visual prognosis is dependent on the concentration, quantity, and pH of the chemical involved as well as the timing and efficacy of treatment. Here we report a case of severe ocular alkali injury in effort to bring attention to the need for early recognition during the advanced burn life support evaluation.The patient is a 22-year-old factory worker who sustained 29.5% partial and full thickness burns while carrying a bucket of powdered magnesium. The magnesium contacted water and ignited onto his face, trunk, and arms. He was initially evaluated in a rural setting where he was immediately intubated and sedated prior to transfer to the regional burn center. Attention was paid to extremity and trunk injuries, however, ocular evaluation and irrigation was not performed until his arrival at the burn center, approximately 6 h later. At that point, he was found to have molten magnesium adhered to bilateral corneas. The patient unfortunately sustained irreversible ocular injury despite amniotic membrane grafts. Awareness of the importance of ocular evaluation during burn resuscitation must be raised in tertiary care centers, emergency medicine, and burn center communities.